From Agricultural Research to Agronomy Research in Francophone Countries of Sub-Saharan Africa and Madagascar between 1945 and 1985 - (:unkn) unknown (My University, 2019)
From the publications of agronomy researchers working in French-speaking countries of sub-Saharan Africa and Madagascar, this article describes the evolution of thought in this discipline between 1946 and 1984. Initially, the desire to quickly make available to farmers and planters results to intensify the practices will lead to many experimental trials of transposed crop techniques of agriculture in temperate countries. The know-how of local farmers will be given little consideration. Gradually, faced with the difficulties encountered in applying these unsuitable techniques, the researchers will engage in work aimed more at understanding the functioning of plant communities and cropping systems, benefiting from advances in agronomic theory and methods of increasing more elaborate to analyze these operations.
Keywords: African Research